Health Education to Promote and Prevent Tinea Cruris at Darul Fadhli Elementary School Palembang City - Ahmad Ghiffari; Resy Asmalia; Raden Pamudji; Heni Nurdita (Indonesia Berdaya, 2022)
Tinea cruris is an infectious disease caused by fungal microorganisms that cause severe itching and secondary infection complaints. Skin disease transmission factors in the groin (tinea cruris) include agent, environmental, and host factors. Tinea cruris disease in elementary school students can reduce academic quality. This activity aims to socialize students in tackling the fungal disease infestation. It will increase knowledge about skin diseases, both in terms of knowledge of parasites/fungus and clean and healthy living behavior towards the incidence of tinea cruris. Community service methods include the delivery of material about personal hygiene, distribution of leaflets, post-test, and pre-test. The activity was carried out on March 8, 2022, and initial measurement of the knowledge and behavior of personal hygiene was carried out, followed by all 55 elementary school students. A questionnaire is an instrument to measure the level of knowledge, behavior, and incidence of tinea cruris. The mean value of the pre-test was higher than the mean score of the post-test. It was concluded that the activity could increase knowledge. It is necessary to collaborate with others, such as health monitoring and collaboration with the community health center.